Silva, Joseli Maria; Ornat, Marcio José y Chimin, Alides Baptista (Jr.) (2013). Geografias malditas: corpos, sexualidades e espaços - Rossi, Rodrigo (Documents d'Anàlisi Geogràfica, 2015)
Silva, Joseli Maria; Ornat, Marcio José y Chimin, Alides Baptista (Jr.) (2013) Geografias malditas: corpos, sexualidades e espaços Ponta Grossa: Toda Palavra, 400 p. ISBN 978-85-62450-29-7